(untitled) (Communication & Society, 2015)
Most young people today are digital natives where the use of new media, is issued by the participation in a creative way and with a high degree of interaction. The emergence of tools making it easy without having high digital skills, has led the grown of prosumers. The aim of the paper is the analysis of the different profiles of this typology of users within the Madrid universities and its interest is settle not only to inquire about the convergent use of technology but also if their interests and motivations really focus on the consumption of new media content or if they participate in a creative way through new technologies, establishing new patterns that enhance interactivity and new business models in media.